Interlingual Errors in Indonesian EFL learners' Pronunciation: From Minimal Pairs to Speaking Ability: - Sayogie, Frans; Adbaka, Muhammad Fadhli (Elsya : Journal of English Language Studies, 2022)
The majority of previous research observed phonemes produced individually to examine errors. As a result, based on the concept of minimum pairings, this study offered a novel way of assessing interlingual errors based on the concept of minimal pairings. This study examines the interlingual errors in consonant minimal pairs to see the correlation between the errors and the speaking ability that happened to high school students. There are several consonants which are being used such as /v/, /θ̠/, /ð̠/, /ʃ/, /t̠ʃ/, /ʤ/, /f/, /t/, /d/, /z/, and /s/ as indicators to find the interlingual errors. This study is descriptive qualitative research that examines the interlingual errors produced by high school students when utilizing English minimal pairs of consonants. All of the consonants acted as the test tool for the 19 selected students in the form of 10 minimal pairs. The research found that students did have difficulties when they were pronouncing the consonant minimal pairs such as /d/ & /ð/, /f/ & /v/, and /ʃ/ & /t̠ʃ/. Thus, the difficulties that occurred in the students’ pronunciation also generate speaking ability between students based on the interlingual errors. The findings showed that high school students mostly struggled with their pronunciation when uttering consonants that do not exist in the Indonesian language. In conclusion, interlingual errors play an important role as a method in teaching a foreign language to see the consonant errors happen in high school students when pronouncing the English language.